Implementation of TBL with constructivist and discovery learning approaches to enhance eco-literacy of homeschooling students - Meryantie, Anggarilia; Nuril Huda; Victor Maruli Tua L. Tobing; Muhajir, Muhajir (Jurnal Inovasi Teknologi Pendidikan, 2025)
The escalating ecological crisis demands an immediate educational response, especially for younger generations. Eco-literacy, the ability to understand ecological systems, think critically about environmental issues, and adopt responsible behaviors, needs to be cultivated early through contextual and transformative learning. This study explores the implementation of a Technology-Based Learning (TBL) model, grounded in constructivist and discovery approaches, to enhance eco-literacy among homeschooling students aged 10–13 years. Using a descriptive qualitative case study, three homeschooling students and two parents at Rumah Ulin, a family-based learning environment integrating ecological values and digital technology, participated as informants. Data were collected retrospectively through participant observation, semi-structured interviews, student reflections, and documentation of prior learning activities. Findings show significant development in four eco-literacy dimensions: ecological awareness (recognition of human–environment relationships), environmental knowledge (understanding of concepts and issues), ecological attitudes (care, responsibility, and commitment to sustainability), and ecological actions (environmentally friendly practices such as reducing plastic use and managing waste). These results demonstrate that technology-based, learner-centered strategies can foster meaningful ecological understanding in non-formal contexts. Future research with larger, more diverse participants and longitudinal designs is recommended to strengthen generalizability and assess long-term impacts.